Matrix Metalloproteinase 13 (MMP13) Is a Direct Target of Osteoblast-Specific Transcription Factor Osterix (Osx) in Osteoblasts - Zhang, Chi; Tang, Wanjin; Li, Yang (PLOS ONE, 2012)
Osterix (Osx) is an osteoblast-specific transcription factor required for bone formation and osteoblast differentiation from mesenchymal stem cells. In Osx-null mice, no bone formation occurs. Matrix metalloproteinase 13 (MMP13) is a member of the matrix metalloproteinase family and plays an important role in endochondral ossification and bone remodeling. Transcriptional regulation of MMP13 expression in osteoblasts is not well understood. Here, we provide several lines of evidence which show that MMP13 is a direct target of Osx in osteoblasts. Calvaria obtained from Osx-null embryos displayed dramatic reductions in MMP13 expression compared to wild-type calvaria. Stable overexpression of Osx stimulated MMP13 expression in C2C12 mesenchymal cells. Inhibition of Osx expression by siRNA led to downregulation of MMP13 expression. Mechanistic approaches using transient transfection assays showed that Osx directly activated a 1 kb fragment of the MMP13 promoter in a dose-dependent manner. To define the region of the MMP13 promoter that was responsive to Osx, a series of MMP13 promoter deletion mutants were examined and the minimal Osx-responsive region was refined to the proximal 80 bp of the MMP13 promoter. Additional point mutant analysis was used to identify one GC-rich region that was responsible for MMP13 promoter activation by Osx. Gel Shift Assay showed that Osx bound to MMP13 promoter sequence directly. Chromatin immunoprecipitation assays demonstrated that endogenous Osx was associated with the native MMP13 promoter in primary osteoblasts in vivo. Taken together, these data strongly support a direct regulatory role for Osx in MMP13 gene expression in osteoblasts. They further provide new insight into potential mechanisms and pathways that Osx controls bone formation.